Origins and evolution of biological novelty - Carscadden, Kelly A.; Batstone, Rebecca T.; Hauser, Frances E. (Biological reviews of the Cambridge Philosophical Society, 2023)
ABSTRACT Understanding the origins and impacts of novel traits has been a perennial interest in many realms of ecology and evolutionary biology. Here, we build on previous evolutionary and philosophical treatments of this subject to encompass novelties across biological scales and eco‐evolutionary perspectives. By defining novelties as new features at one biological scale that have emergent effects at other biological scales, we incorporate many forms of novelty that have previously been treated in isolation (such as novelty from genetic mutations, new developmental pathways, new morphological features, and new species). Our perspective is based on the fundamental idea that the emergence of a novelty, at any biological scale, depends on its environmental and genetic context. Through this lens, we outline a broad array of generative mechanisms underlying novelty and highlight how genomic tools are transforming our understanding of the origins of novelty. Lastly, we present several case studies to illustrate how novelties across biological scales and systems can be understood based on common mechanisms of change and their environmental and genetic contexts. Specifically, we highlight how gene duplication contributes to the evolution of new complex structures in visual systems; how genetic exchange in symbiosis alters functions of both host and symbiont, resulting in a novel organism; and how hybridisation between species can generate new species with new niches.